Production et productivité des copépodes pélagiques des eaux roumaines de la Mer Noire - Porumb, Florica (Cercetări Marine - Recherches Marines, 2026)
Based on 780 zooplankton samples collected during I970 - 1975 along a transect East Constanta to 30 sea miles and 50m depth, the production and the specific productivity of 6 species of pelagic copepods have been studied. The daily, seasonal, and annual mean rate of the copepods production and specific productivity are discussed in the paper.